2004
DOI: 10.1002/cncr.20484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin B12, folate, and dietary supplements on breast carcinoma chemotherapy–induced mucositis and neutropenia

Abstract: BACKGROUNDAlthough patients with malignant disease frequently use dietary supplements, the effects of these agents with regard to chemotherapy are unclear. Therefore, the authors investigated the influence of vitamin B12, folate, and nutritional supplements on chemotherapy‐induced toxicity.METHODSWomen with breast carcinoma were asked to complete a questionnaire that recorded their use of dietary supplements. Blood samples were obtained for the assessment of serum vitamin B12 and folate levels before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 60 publications
2
30
1
1
Order By: Relevance
“…The release behavior of KA from the KA-CS-MNPs and KA-PEG-MNPs nanocomposites can be described by different kinetics models, pseudo first-order (Equation 2), 60 ln (q e -q t ) = ln q e -kt (2) t/q t = 1/k q e 2 + t/q e (3)…”
Section: In Vitro Release Study Of Ka From the Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…The release behavior of KA from the KA-CS-MNPs and KA-PEG-MNPs nanocomposites can be described by different kinetics models, pseudo first-order (Equation 2), 60 ln (q e -q t ) = ln q e -kt (2) t/q t = 1/k q e 2 + t/q e (3)…”
Section: In Vitro Release Study Of Ka From the Nanocompositesmentioning
confidence: 99%
“…It is given to patients for treatment, or it may aim to prolong lifetimes or to palliate cancer symptoms. Traditional chemotherapy has limitations such as immunosuppression, 1 mucositis, 2 and alopecia. 3 These limitations are due to the nonselectivity of antineoplastic drugs, thus affecting normal cells as well as cancerous cells.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative phytochemical screening showed that tannins and polyphenols were the most abundant phytochemicals present in both leaf extracts as shown on Table 3. Alkaloids have shown efficient therapeutic properties asan anticancer, analgesic, antispasmodic and antibacterial properties (Yakubu et al, 2009;Branda et al, 2004). Both natural and synthetic alkaloids have been used as basic medicinal agent.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
“…The leaves (either fresh or dried) are cooked into a thick viscous soup or added to stew or soup and are rich sources of vitamins and minerals (Branda et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation